Deep Neural Network Structure to Improve Individual Performance based Author Classification - Firdaus, Firdaus (Computer Engineering and Applications Journal, 2019)
This paper proposed an improved method for author name disambiguation problem, both homonym and synonym. The data prepared is the distance data of each pair of author’s attributes, Levenshtein distance are used. Using Deep Neural Networks, we found large gains on performance. The result shows that level of accuracy is 99.6% with a low number of hidden layers